2020
DOI: 10.1098/rsos.200480
|View full text |Cite
|
Sign up to set email alerts
|

Experimental infection of bumblebees with honeybee-associated viruses: no direct fitness costs but potential future threats to novel wild bee hosts

Abstract: Pathogen spillover represents an important cause of biodiversity decline. For wild bee species such as bumblebees, many of which are in decline, correlational data point towards viral spillover from managed honeybees as a potential cause. Yet, impacts of these viruses on wild bees are rarely evaluated. Here, in a series of highly controlled laboratory infection assays with well-characterized viral inocula, we show that three viral types isolated from honeybees (deformed wing virus genotype A, deformed wing vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 85 publications
2
46
0
Order By: Relevance
“…The fact that viruses are present, which show similar patterns amongst hosts, suggests that, if an event such as the introduction of a novel transmission route occurs for one of these viruses, there may be significant risk to diverse hosts. This is especially concerning as at least BQCV, SBV and IAPV are known to also replicate in diverse hosts [49][50][51] and we still know relatively little about three of the more abundant viruses in this study (MV, MiV, HsAV). Another unusual finding of this study was the notable absence of BQCV and SBV in the honey bee population, a contrast to the majority of studies [52,53].…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…The fact that viruses are present, which show similar patterns amongst hosts, suggests that, if an event such as the introduction of a novel transmission route occurs for one of these viruses, there may be significant risk to diverse hosts. This is especially concerning as at least BQCV, SBV and IAPV are known to also replicate in diverse hosts [49][50][51] and we still know relatively little about three of the more abundant viruses in this study (MV, MiV, HsAV). Another unusual finding of this study was the notable absence of BQCV and SBV in the honey bee population, a contrast to the majority of studies [52,53].…”
Section: Discussionmentioning
confidence: 94%
“…[47] and hornets (Vespa velutina) [48], conclusive studies on the ability of DWV to cause pathology in non-honey bee hosts have largely been limited to bumblebees [15,19]. Another recent study, however, found no effect on mortality in experimentally infected bumblebees [49], suggesting that DWV infection is not uniformly virulent in bumblebees. As such, DWV is clearly well-adapted and has a diverse and wide insect host range.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A series of experimental infections have shown that three viral types isolated from honeybees (DWV genotype A, DWV genotype B and BQCV) readily replicate within hosts of the bumblebee B. terrestris . Impacts of these honeybee-derived viruses—either injected or fed—on the mortality of B. terrestris workers were negligible and probably dependent on host condition [ 27 ]. The identification and sequencing of an individual strain of honeybee viruses in bumblebee cannot be directly linked to the possible pathology but help us to understand the spillover events between different species.…”
Section: Discussionmentioning
confidence: 99%
“…Seven of these viruses are known to induce measurable symptoms, such as the Deformed wing virus (DWV), which has been associated with colony losses [ 22 , 23 , 24 , 25 , 26 , 27 ]. This virus has three main variants, DWV-A, DWV-B and DWV-C with still debated respective virulence [ 28 , 29 , 30 , 31 , 32 , 33 , 34 ], and several recombinant variants have also been described [ 35 , 36 , 37 , 38 , 39 , 40 ]. Black queen cell virus (BQCV) and Sacbrood virus (SBV) can impair the developmental stages.…”
Section: Introductionmentioning
confidence: 99%